Does the fish-infecting Trypanosoma micropteri belong to Trypanosoma carassii? - Zhang, Peng; Chen, Ke; Svobodova, Michaela; Yang, Ting-Bao; Lukes, Julius; Zhang, Jinyong; Lun, Zhao-Rong; Lai, De-Hua (Folia parasitologica, 2022)
Recently, based on a limited morphological characterisation and partial 18S rRNA gene sequence, Jiang et al. (2019) described Trypanosoma micropteri Jiang, Lu, Du, Wang, Hu, Su et Li, 2019 as a new pathogen of farmed fish. Here we provide evidence based on the expanded sequence dataset, morphology and experimental infections that this trypanosome does not warrant the establishment as a new species, because it is conspecific with the long-term known Trypanosoma carassii Mitrophanow, 1883, a common haemoflagellate parasite of freshwater fish. The former taxon thus becomes a new junior synonym of T. carassii.
Keywords: Trypanosomiasis; Fresh Water; trypanozomiáza; Trypanosomes; morphological data; 18S rRNA gene; sladká voda; synonymy; RNA ribozomální 18S; zvířata; classification; fylogeneze; host ranges; RNA, Ribosomal, 18S; Fishes; Trypanosoma; ryby; Phylogeny; fish; Animals